TEKNIK PENGOLAHAN SELAI TOMAT SEBAGAI MEDIA BELAJAR DAN DUKUNGAN BAGI UMKM PANGAN LOKAL DI SMA KRISTEN PONTAK, MINAHASA SELATAN - Rostina Melpin; Citra C Dusun; Filan O Mandang; Christine P Lomo; Yuannita Aida (Jurnal Pengabdian Ibnu Sina, 2026)
The Community Service Program (CSP) on tomato jam processing techniques at SMA Kristen Pontak, SouthMinahasa, was implemented as a solution to the abundant tomato harvests that are often not absorbed by themarket, reducing farmers’ economic value. The main problems faced by partners include limited knowledge ofproduct diversification, food hygiene standards, and basic marketing strategies. The objective of this program isto improve the skills of students, teachers, and local MSMEs in processing tomatoes into hygienic, durable, andmarketable jam products, while strengthening collaboration between schools and communities in local economicempowerment. The method applied was a participatory approach through five stages: preparation, socialization,training and demonstration, mentoring implementation, and evaluation and dissemination. Evaluation wasconducted using pre-test and post-test to measure improvements in participants’ knowledge and skills. Resultsshowed significant progress, with the average pre-test score of 57 increasing to 82 in the post-test, reflecting a44% improvement. The highest increase was observed in simple marketing strategies, rising from 50 to 78 (a 56%gain), followed by food hygiene from 55 to 80, and processing techniques from 58 to 83. The program successfullyproduced trial tomato jam products with simple yet marketable packaging and established collaborative networksbetween schools and MSMEs. Overall, this initiative provided positive impacts in education through practice-based learning and strengthened the capacity of local food MSMEs, serving as a replicable model forentrepreneurship development based on local resources.